THE AGILE EARNED VALUE MANAGEMENT METHOD AS A COST MANAGEMENT TOOL IN SCRUM PROJECTS: Array - Lysenko, D.; Fediai, Y. (Municipal economy of cities (Technical science), 2021)
According to the statistics, the majority of IT projects run 50–150 percent over budget, which indicates the importance of managing its cost. In agile methodologies which are widely used in software development, little attention is given to cost management. Lack of specialized cost management tools in agile practices raises the question of the feasibility of adapting traditional project management methods and techniques. The purpose of the research is to improve the quality of IT projects cost control processes by developing a project cost management model using the Agile Earned Value Management method. The paper discusses the EVM techniques which have been adopted to provide the benefits of traditional EVM in Agile projects. There are some misconceptions that EVM techniques are too difficult to perform effectively on projects implemented using agile approaches (i.e. Scrum framework). The challenges are primarily associated with the fact that the EVM method requires creating a complete description of project tasks and a detailed schedule of their execution at the initial stage allowing accurate estimates of the actual data and monitoring the project progress from start to completion. On the other hand, Scrum emphasizes the need for incremental, multi-level planning and discourages planning software projects down to the lowest level of decomposition in the early stages. The reason for this is the high degree of ambiguity inherent in complex software systems, and the high probability of changes that make fully defining the requirements up front nearly impossible. However, upon closer examination of Sprint attributes, such as fixed duration, fixed backlog, cost measurement of sprint tasks, the ultimate goal of delivering a minimum viable product – leads us to the conclusion that Sprint can be considered as a subproject to which the mechanism of the EVM method can be applied using the same metrics. The paper further summarizes the main provisions and guidelines of the AgileEVM method, based on which its process model is developed. The inputs of the model are initial release baseline parameters and data captured at the completion of each Sprint: Planned Sprints (PS); Planned Release Points (PRP); Budget at Complete (BAC); Points Completed (PC), Points Added (PA), and Sprint Cost (SC). The controls are the AgileEVM method guidelines. The mechanisms are project manager and necessary software (MS Excel, MS Project). At the output of the model we obtain forecast indicators: Estimate to Complete (ETC), Estimate at Complete (EAC), Number of Total Sprints (N), and Release Date (RD). The final conclusion of the conducted research is that the application of the Earned Value Management method to projects implemented with Scrum enables the project manager and the project team with a valuable tool to monitor the progress of their work and to take appropriate measures.